Swedish supporter culture - restrictions, conflicts, resistance - Karlen, S.; Radmann, A. (Soccer & Society, 2023)
This study investigates the conflict between, on the one hand, the Swedish police and law enforcement and, on the other, supporters, football clubs, and the organization of Swedish Elite Football. The core of this conflict is the introduction of a new structure for maintaining order, referred to as the Condition Ladder (Villkorstrappan), aimed at addressing disturbances and pyrotechnics in the stands. The aim of this article is to chart and analyse the impact of the Condition Ladder on Swedish football culture. The methods are media analysis, analysis of police documents and interviews. The study confirms previous findings regarding the role of the media in public discourse, but also indicates that the previously negative media image of the supporter culture has changed into a more positive view. The study shows that the new restrictions create conflicts and tensions between the involved actors when these actors are to handle risk elements in Swedish supporter culture.